The darkest minds - Bracken, Alexandra (Bracken, Alexandra. Darkest minds, 2012)
"Sixteen-year-old Ruby breaks out of a government-run 'rehabilitation camp' for teens who acquired dangerous powers after surviving a virus that wiped out most American children"--